The Influence of Brand Image and Price on Toyota Avanza Car Purchasing Decision - Bakri, Muhammad (Advances in Business & Industrial Marketing Research, 2023)
Purpose: This study investigates the impact of brand image and price on the decision to purchase Toyota Avanza cars in Indonesia. The research aims to determine which factor—brand image or price—strongly influences consumer behavior and whether brand image mediates the relationship between price and purchase decision. Research Design and Methodology: Data were collected from 384 respondents through structured questionnaires using a quantitative descriptive approach. The sample consisted predominantly of males aged 25-35, a key demographic in the automotive market. The study employed Confirmatory Factor Analysis (CFA) to ensure construct validity and Cronbach's Alpha to confirm reliability. Multiple linear regression and path analysis were conducted to examine the relationships between variables. Findings and Discussion: The analysis revealed that brand image and price significantly affect purchase decisions, with brand image having a more substantial impact. Furthermore, path analysis demonstrated that brand image is a mediator between price and purchase decision, indicating that the perception of brand value enhances the influence of price on consumer choices. Implications: These findings have significant implications for automotive companies. They suggest that to effectively influence consumer behavior, companies should prioritize enhancing their brand image over engaging in price competition. This study makes a substantial contribution to marketing strategy development in the automotive sector. It also recommends future research that incorporates longitudinal designs and additional variables, such as cultural and psychological factors, to better understand consumer decision-making processes across different markets.